Crocus ancyrensis subsp. guneri (Iridaceae), a new subspecies from Turkey - Yüzbaşioğlu, Sirri; Celep, Ferhat (Phytotaxa, 2016)
Crocus ancyrensis subsp. guneri is described and illustrated as a new subspecies from Amasya province in Northern Anatolia. A description, detailed illustrations, photographs of metaphase plate and SEM micrographs of seed surface sculpturing pattern are presented. The new subspecies differs from the type subspecies by its prominent flower colouration. While the new subspecies has constantly and intensively suffused or striped with purplish-brown colour on the outer side of the outer perigone segments, the type subspecies always lacks any coloration on the outer side of the outer perigone segments.